Multimodal analysis of film and video production: reviewing the field - Marwa Mohamed Abd Allah; Marwa Mohamed Khamis El-Zouka; Abeer M. Refky M. Seddeek (Insights into Language, Culture and Communication, 2025)
It has been found that the literature on film analysis primarily contains four proposed attempts at applying multimodal terms, techniques, and procedures to film and video production: O’Halloran (2004), Tan (2009), Baldry and Thibault (2006), and Bateman (2008, 2012). The core insight and principle these four models share is how semiotic resources or choices are combined together and interact to produce meaning. They all emphasise, each to their own, that semiotic resources, or modes are organised into a hierarchy of systems, planes, strata, or taxonomies where semiotic features can be identified, classified, and analysed to form patterns and connections that ultimately lead to a better understanding and interpretation of multimodal phenomena. In addition, they highlight the importance of global coherence, and how it is achieved through the repeated co-deployment of semiotic modes to form patterns in dynamic texts. The four frameworks touch upon the notion of genre, and how patterns of intersemiotic relations can be instrumental in identifying genres. Finally, they point out that the construction of meaning in dynamic texts is impacted by how the text unfolds in real time.   Keywords: Multimodal analysis; Film analysis Received on: 11 November 2024 Accepted on: 19 December 2024 Published on: 06 April 2025